The Use of Gamification in Occupational Therapy Education. - Mulligan, Chris; Bennett, Leslie; Graves, Donald F. (Open Journal of Occupational Therapy (OJOT))
Gamification is an approach to game-based learning, also called educational games. These fun supplemental tools are infused into K-12 and higher education curriculums. This study aimed to discover faculty and student perspectives and explore gamification or game-based learning in accredited occupational therapy graduate programs through the lens of faculty (n = 47) and students (n =54). The primary researcher distributed two anonymous surveys: Survey 1 to current faculty and Survey 2 to students in occupational therapy programs, examining their use of game-based learning tools. The findings revealed that most faculty (n = 38, 85%) and students (n = 48, 92%) use gamification, such as Kahoot!, Quizlet, and Jeopardy, in their accredited programs. Ninety-six percent of OT students and 98% of OT faculty in graduate programs found gamification beneficial in their courses, which enhances student engagement and learning; however, faculty noted that the time required to set up these supplemental educational tools is a limiting factor.